2020
DOI: 10.15244/pjoes/106031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mathematical Models in Nitrogen Transfer to Overland Flow Subjected to Simulated Rainfall

Abstract: The chemical transfer from soil to runoff leading to nutrient loss of sloping farmland has been recognized as a major threat to soil fertility and receiving water bodies [1-3]. There is most concern regarding nitrogen (N) transfer, as it is increasingly applied to boost crop yields producing eutrophication in surface waters [4, 5]. Accordingly, many field, laboratory and modeling works have been undertaken in an attempt to investigate N loss and transfer via overland flow and propose mitigation methods [5, 6].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, purple soil slopes account for 70% of the total farmlands in the Three Gorges Reservoir Area along the Yangtze River (Ma et al, 2016). There is evidence that NH4-N, NO3-N and TN from sloping farmlands of purple soils can be exported in large numbers subjected to various slope gradients and rainfall intensities (Ding and Zhang, 2009;Jia et al, 2007;Xie et al, 2020;Xu et al, 2011;Zhao et al, 2015). Xu et al (2011) reported that N losses due to sediment transport accounted for 53%~62% of total N losses from field observations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, purple soil slopes account for 70% of the total farmlands in the Three Gorges Reservoir Area along the Yangtze River (Ma et al, 2016). There is evidence that NH4-N, NO3-N and TN from sloping farmlands of purple soils can be exported in large numbers subjected to various slope gradients and rainfall intensities (Ding and Zhang, 2009;Jia et al, 2007;Xie et al, 2020;Xu et al, 2011;Zhao et al, 2015). Xu et al (2011) reported that N losses due to sediment transport accounted for 53%~62% of total N losses from field observations.…”
Section: Introductionmentioning
confidence: 99%